The Salad Days of the EU Digital Service Tax - Nugroho, Adrianto Dwi (Indonesian Comparative Law Review, 2019)
Responding to a series of aggressive tax planning allegedly committed by multinational corporations running their businesses on digital platforms, states have drafted laws that would enable them to impose additional taxes on such corporations. In the EU, the proposal for a Council Directive on the Digital Services Tax (DST) projects for a 3% tax chargeable on the revenues generated by corporations surpassing a certain threshold of global and EU yearly revenues. The initial plan is to tax these corporations with respect to their online placement of advertising, enabling of online marketplaces, and sales of collected user data. While the EU organs are still undergoing the due legislative processes on the proposal, two flaws of the DST may be argued, namely that it conflates features of direct taxes (i.e. income tax) with that of indirect taxes (i.e. value added tax); and that it embeds covert discriminatory measures against certain multinational corporations. The maturation of the DST depends on the formulation of sound legal principles and ingenious concept which would hallmark a DST regime from the corporate income tax one.